Estoques parciais e redução de perda de carbono com a substituição da queimada pela fosfatagem num agroecossistema de Brachiaria brizantha cv. Marandu em oxissolo na Amazônia Ocidental - Silva, Luiz Carlos da (2017)
For decades, cattle production in Brazil has been done at the expense of gradual pasture degradation. The burnings are among the causes of this degradation and its spread aggravates the problem. The practice of the Humaita cattle ranchers who use the burn to eliminate weeds and improve the pastures contrasts with the discovered and chemically degraded soils cultivated with B. brizantha Stapf. cv. Marandu of low productivity and invaded by these weed plants. In opposition to that arise the types of management that increase the surface biomass, the stored C and the nutrient recycling in the pasture. Among these, it can mentioned the phosphating in substitution to the burning, which would allow the insertion of P and other nutrients in the soil with increasings in the biomass productivity and C retention in the pasture agroecosystem. An experiment consisting of 5 treatments with 4 replicates was established in the field, being: T1: pasture without burning; T2: pasture without burning + low level of phosphating; T3: pasture without burning + high level of phosphating; T4: pasture without burning + very high level of phosphating, and; T5: pasture burned. The aim of this work was quantify the soil chemical fertility attributes, with emphasis on phosphorus, the biomass productivity, partial carbon stocks and the reduction of partial losses of the element to the atmosphere as a function of the replacement of burning by phosphating of a degraded B. brizantha Stapf. cv. Marandu agroecosystem in the annual initial growth in the Western Amazon. The phosphating in substitution to the burning improved the soil fertility with a consequent increase in the biomass yields with a consequent increasings in the yields of current partial biomass and current partial biomass remaining, increasing, as a result, the current partial carbon stock and the remaining partial carbon stock which were reflected on a significant reduction of CO2 losses to the atmosphere in the initial of annual plant growth.